Review: RNA therapy for type 1 & 2 diabetes - Bintang, Muhamad Ilham; Asnawi, Aiyi; Agita, Widhiya (Science Midwifery, 2024)
Diabetes is a group of metabolic disorders with high blood glucose levels. In type 1 diabetes, blood glucose increases due to damage to pancreatic beta cells. In type 2 diabetes, insulin production is ineffective in glucose uptake into target tissues, increasing glucose levels. Advances in RNA-based technologies indicate that RNA molecules have multiple roles in disease initiation and progression. This review discusses recent developments in RNA therapy for type 1 and type 2 diabetes. RNA therapies, such as mRNA, miRNA, siRNA, lncRNA, and circRNA, show great potential. mRNA and miRNA are important in pancreatic cell development, insulin resistance, insulin sensitivity, and insulin secretion. siRNA improves glucose regulation and improves beta cell dysfunction in T1D and T2D. lncRNAs regulate beta cell responses to inflammation and insulin resistance. circRNA plays a role in M1 macrophage activation associated with T1D pathogenesis and regulation of insulin transcription and secretion. RNA therapy offers revolutionary possibilities in the management and potential cure of type 1 and type 2 diabetes. It is believed to improve and change the clinical approach to diabetes, with research continuing to develop therapies that are safe, effective, and able to change the paradigm of diabetes treatment.